نقد على نظرية التوحيد أنتروفوسينتريس عند حسن حنفي - Harda Armayanto; Syamsul Hadi Untun; Farida Septian (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2019)
Tawheed as known and believed by Muslims is to declare that God as the only purpose in worship. According to Hasan Hanafi, a concept tauheed in Islam has made Muslims retarded. Therefore, a Muslims are left behind Westerns. Hanafi then offers another kind of tawheed which he calls by the Antropocentric Tawheed. Hanafi considers that God is no longer became as the center of everything. In Hanafi’s opinion, the main center of everything is human. The aim is to make a muslims advanced as Westerns. In Hanafi’s view, the Westerns advancied because they has liberated them self from religion (God). The purpose of this research is to reveal the concept and relevance of Hasan Hanafi’s Antropocentric Tauhid, and then to criticize it. By using descriptive method and critical analysis, in the end it was found that Hanafis thought is ambiguous. In the terms of terminology, the name of the Anthropocentric Tauhid that triggered the problem, so it takes a deep and systematic criticism to prove the error of this Hanafi idea.